On the Hecke’s Z-functions and the prime number’s distribution in the algebraic quadratic immaginary number field - Bulota, K. (Lithuanian Mathematical Journal, 1964)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:К. Булота. О Z-функциях Гекке и распределении простых чисел мнимого квадратичного поляK. Bulota. Apie Hekės Z-funkcijas ir kvadratinio menamo skaičių kūno pirminių skaičių pasiskirstymą